Kesan Kurang Tumpuan Terhadap Prestasi Kerja Pemandu Kereta Api: Kajian Kes di Syarikat Kereta Api Malaysia: Kajian Kes di Syarikat Keretapi Malaysia - Saperi, Nurul Nadhirah; Abdullah, Nor Hazana; Abdul Hamid, Nor Aziati (Research in Management of Technology and Business, 2022)
Rail services have become the backbone of the existing public transport system. However, there are several problems about train driver performance such as lack of focus, which could lead to accidents. Therefore, this study examined the effects of driver; attention (or lack of) on Syarikat Keretapi Malaysia (SKM) drivers’ performance. Questionnaires were distributed to all 100 ETS drivers working using purposive sampling. Only 81 ETS drivers responded to yield a return rate of 81% According to the findings, the attention and the driver performance are high. There is significant association between attention and driver performance. This indicates that important to reduce secondary task during driving to increase attention and improve performance. The expected results of this study would indicate that there is a significant relationship between driving focus and the performance of train drivers.